The Moderation Effect of Psychological Empowerment on The Relationship of Comprehensive Performance Measurement System With Managerial Performance - Kevin Hermanto Tupamahu; Cynthia Petra Haumahu; Criezta Korlefura (International Journal of Education, Information Technology, and Others, 2023)
This study aims to examine and obtain empirical evidence regarding the moderating effect of psychological empowerment on the relationship between comprehensive performance measurement systems and managerial performance.The sample for this research is all levels of managers at the Bank in Ambon City. The sample was selected using the judgment sampling method, with the criteria of having experience as a manager for at least three years. Data collection was carried out through questionnaires which were directly submitted to business unit managers. A total of 100 questionnaires were successfully collected, and 98 questionnaires that could be used. Data were analyzed to test the hypothesis using multiple linear regression.The results of the study show that a comprehensive performance measurement system has a positive and significant effect on managerial performance; and psychological empowerment acts as a variable that moderates the relationship between a comprehensive performance measurement system and managerial performance.